2019
DOI: 10.1093/ageing/afz033
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between self-reports, proxy-reports and the National Patient Register regarding diagnoses of cardiovascular disorders and diabetes mellitus in a population-based sample of 80-year-olds

Abstract: Background cognitive impairment is common among older adults, necessitating the use of collateral sources in epidemiological studies involving this age group. The objective of this study was to evaluate agreement between self- and proxy-reports of cardiovascular disorders and diabetes mellitus in a population-based sample of 80-year-olds. Further, both self- and proxy-reports were compared with hospital register data. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 33 publications
12
17
0
Order By: Relevance
“…However, we had the possibility to include proxy informants, register data and information from ECG. In another study, we found a substantial agreement between proxy‐ and self‐reported history of atrial fibrillation . Thus, we believe that we were able to detect most cases of atrial fibrillation.…”
Section: Discussionsupporting
confidence: 55%
“…However, we had the possibility to include proxy informants, register data and information from ECG. In another study, we found a substantial agreement between proxy‐ and self‐reported history of atrial fibrillation . Thus, we believe that we were able to detect most cases of atrial fibrillation.…”
Section: Discussionsupporting
confidence: 55%
“…We have previously validated self-reported AF diagnoses in the H70-studies against register data and found a substantial agreement between the two sources (Kappa=0.61). 43 However, some limitations should also be recognized. First, this study has a cross-sectional design, which does not allow us to assess causal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…This study is based on data drawn from several Swedish population registers, namely the register of the total population, the National Patient Register and the Swedish Cancer Register [16][17][18][19][20]. The data covers all men and women over the age of 60 who were residing in Sweden at any point in time during 1994 and 2016.…”
Section: Datamentioning
confidence: 99%